Smartphone use and addiction among secondary school students in Kuantan, Malaysia - Siew, Pien Lee; Zamimi, Hanis Athirah; Syed Elias, Sharifah Munirah; Atan, Ashikin; Makhdzir, Norafisyah (I I U M Press, 2021)
Background: Smartphone addiction has become a social problem in Malaysia as smartphone users increase drastically. Previous study revealed that smartphone addiction has a negative effect on the physical and psychosocial of a human being. Aims: This study aims to examine smartphone use and addiction among secondary school students. Methods: A cross-sectional study was employed involving 203 secondary school children at a secondary school in Malaysia. A set of a questionnaire consisting of two parts was used; (1) Part A: Sociodemographic, (2) Part B: Smartphone Addiction Scale in Malay version (SAS-M). Results: Finding from this study showed that there was a long duration of smartphones use was detected during the weekend with more than three hours per day and social media (81.8%) was the frequently visited function in the smartphones. These group of students were not addicted to smartphones, however, more than half of the students (57.6%) have a high risk of smartphones addiction. There is also a significant negative weak correlation between smartphone use and smartphone addiction during weekday and weekend with (p < 0.05; r2 -0.354, -0.360), respectively. Conclusion: This study provides insight into the use of smartphone and smartphone addiction in secondary school students from a Malaysian perspective.